Further evidence for POMK as candidate gene for WWS with meningoencephalocele - Paul, Luisa; Rupprich, Katrin; Della Marina, Adela; Stein, Anja; Elgizouli, Magdeldin; Kaiser, Frank J; Schweiger, Bernd; Köninger, Angela; Iannaccone, Antonella; Hehr, Ute; Kölbel, Heike; Roos, Andreas; et al. (Université d'Ottawa | University of Ottawa, 2020)
Abstract Background Walker-Warburg syndrome (WWS) is a rare form of alpha-dystroglycanopathy characterized by muscular dystrophy and severe malformations of the CNS and eyes. Bi-allelic pathogenic variants in POMK are the cause of a broad spectrum of alpha-dystroglycanopathies. POMK encodes protein-O-mannose kinase, which is required for proper glycosylation and function of the dystroglycan complex and is crucial for extracellular matrix composition. Results Here, we report on male monozygotic twins with severe CNS malformations (hydrocephalus, cortical malformation, hypoplastic cerebellum, and most prominently occipital meningocele), eye malformations and highly elevated creatine kinase, indicating the clinical diagnosis of a congenital muscular dystrophy (alpha-dystroglycanopathy). Both twins were found to harbor a homozygous nonsense mutation c.640C>T, p.214* in POMK, confirming the clinical diagnosis and supporting the concept that POMK mutations can be causative of WWS. Conclusion Our combined data suggest a more important role for POMK in the pathogenesis of meningoencephalocele. Only eight different pathogenic POMK variants have been published so far, detected in eight families; only five showed the severe WWS phenotype, suggesting that POMK-associated WWS is an extremely rare disease. We expand the phenotypic and mutational spectrum of POMK-associated WWS and provide evidence of the broad phenotypic variability of POMK-associated disease.